Modelling an equivalent b-value in diffusion-weighted steady-state free precession - Tendler, B; Tendler, B; Foxley, S; Cottaar, M; Jbabdi, S; Miller, K (Wiley, 2020)
Purpose: Diffusion‐weighted steady‐state free precession (DW‐SSFP) is shown to provide a means to probe non‐Gaussian diffusion through manipulation of the flip angle. A framework is presented to define an effective b‐value in DW‐SSFP.